International and national coordination of the Schengen evaluation mechanism (Academic Journal of Internal Affairs, 2023)
Aim: The aim of the study is to examine the functioning of the renewed Schengen evaluation mechanism, based on the new Schengen Evaluation Regulation, which entered into force on 1 October 2022 and applies from February 2023, and to present the synergistic cooperation of the key players in the system.Methodology: The research is essentially qualitative, based on document and content analysis (context and innovation analysis), source analysis and interviews with international experts.Findings: It has been found that the functioning of the complex system introduced in the study is linked to a number of international and national actors, who are closely interconnected and ensure the functioning of the Schengen evaluation mechanism in a form of symbiotic relationship. The roles and responsibilities of the key players imply that if one of them malfunctions, the whole system will be damaged. It may be worthwhile in the future to scientifically investigate and explore whether the system has managed to achieve a transformation in which all actors can work together properly, thus contributing to a secure and efficient Schengen area.Value: The study is unique at national level, no similar analysis has been done in the research area before. In addition to the milestones in the development of Scheval and the regulation of the current system, the research also looks at the essential elements of the special relationship between the main international and national actors. The work can provide a good theoretical basis for further studies and analyses.
Keywords: Schengen; Scheval; evaluation mechanism; Schengen cooperation